Economic evaluation of health programs - Basics concepts, methodology, challenges and opportunities (Portuguese Journal of Family Medicine and General Practice, 2008)
This article offers a general perspective on the main methods used on the economic evaluation of health technologies and it describes how these methods help to base the decisions concerning their use on credible scientific evidences obtained through systematic and transparent means. The scientific literature identifies four types of economic evaluation of health programs: cost analysis, cost-effectiveness analysis, cost-utility analysis and cost-benefit analysis. The cost-effectiveness analysis (which measures the consequences on natural units) and cost-utility analysis (which measures the consequences on QALYs: Quality-Adjusted Life Years) are the most frequently analysis used on processes of Evaluation of Health Technologies. When there are no available economic or effectiveness data on an individual level derived from quality clinical essays eligible for use on economic evaluation studies, it is necessary to resort to mathematic models that combine and synthesize all the available evidence. Scientific modelling also permits to extrapolate from intermediate consequences to final consequences or to an adequate time horizon, to incorporate elements of uncertainty and also to extrapolate consequences of the health programs (effectiveness/QALYs) to the real context in which they will be applied. The unavoidable uncertainty associated with every type of economic evaluation must be measured and integrated in the analysis; there are techniques that allow to carry out this goal, providing the politic decision-maker with an assessment of the strength of the economic evaluation conclusions. The most common indicator used to confront costs and consequences in economic evaluation studies is the Incremental Cost-Effectiveness Ratio (ICER). Its estimate and application in the elaboration of the final recommendations of economic evaluation studies will be described on the last chapter of this article.